Palliative Care Education to Enhance Informal Caregivers’ Skills in Caring for Patients with Cancer: A Scoping Review - Effendy, Christantie; Kurianto, Endar; Darmayanti, Anisa Rayu Ike; Noviana, Uki; Nurjannah, Intansari (Scientific Foundation SPIROSKI, 2022)
Background: Living with cancer causes stress for both patients and caregivers. Empowering family caregivers is critical in palliative care. It is well known that a lack of proper knowledge and training of informal caregivers is a barrier to palliative care provision at home.